Does miRNA Expression in the Spent Media Change During Early Embryo Development? - Rio, Paul Del; Madan, Pavneesh (Frontiers in Veterinary Science, 2021)
Distinct miRNA populations have been detected in the spent media of in-vitro culture systems. However, profiling has been limited to media conditioned with blastocyst-stage embryos. Therefore, the aim of the study was to profile extracellular miRNAs throughout the pre-implantation period in bovine embryos. To achieve this, cumulus oocyte complexes were aspirated from ovaries, in-vitro matured, fertilized, and cultured under standard laboratory procedures to the 2-cell, 8-cell, or blastocyst stage of development. At each developmental stage, 25 μl of spent in-vitro culture media was collected, pooled to 300 μl, and processed for total RNA extraction. In-vitro culture media, which never came in contact with any embryos, were additionally processed for total RNA extraction to serve as a negative control. Following hybridization on a GeneChip miRNA 4.0 array, comparative analysis was conducted between spent media and control samples. In total, 111 miRNAs were detected in the spent media samples, with 56 miRNAs identified in blastocyst spent media, 14 miRNAs shared between 8-cell and blastocyst spent media, 7 miRNAs shared between all 3 conditions, and 6 miRNAs exclusive to 2-cell spent media. miRNA-mRNA target prediction analysis revealed that the majority of genes predicted to be regulated by the miRNAs identified in the study have roles in cellular process, metabolic process, and biological regulation. Overall, the study suggest that miRNAs can be detected in the spent media of in-vitro culture system throughout the pre-implantation period and the detected miRNAs may influence genes impacting early embryo development.